2015
DOI: 10.1097/mcc.0000000000000218
|View full text |Cite
|
Sign up to set email alerts
|

What is the ideal crystalloid?

Abstract: Crystalloids, like other types of intravenous fluids, are drugs with important effects on clinical outcomes that may be mediated by osmolality, chloride content, and SID.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…We used lactated Ringer's as the balanced crystalloid, which has a near-physiologic strong ion difference 10 because it contains less chloride than saline, thereby reducing the risk of hyperchloremic metabolic acidosis. 11 Analysis was restricted to the first surgery for each patient. We excluded surgeries lasting less than 2 h, urgent/emergency procedures, and patients with American Society of Anesthesiologists (Schaumburg, Illinois) physical status score 5 or greater, chronic renal failure requiring preoperative dialysis, or missing preoperative creatinine values.…”
Section: Methodsmentioning
confidence: 99%
“…We used lactated Ringer's as the balanced crystalloid, which has a near-physiologic strong ion difference 10 because it contains less chloride than saline, thereby reducing the risk of hyperchloremic metabolic acidosis. 11 Analysis was restricted to the first surgery for each patient. We excluded surgeries lasting less than 2 h, urgent/emergency procedures, and patients with American Society of Anesthesiologists (Schaumburg, Illinois) physical status score 5 or greater, chronic renal failure requiring preoperative dialysis, or missing preoperative creatinine values.…”
Section: Methodsmentioning
confidence: 99%
“…Besides the focus on hemodynamic targets to be achieved in critically ill patients, researchers have shifted their attention to the effects of different categories and types of fluids. Looking from afar at the never-ending debate on the potential benefit of colloids vs. crystalloids [2], we have moved towards the evidence that even the type of both colloids and crystalloids may affect patient-centred clinical outcomes, including survival [3,4].…”
mentioning
confidence: 99%
“…In the SOAP study, positive balance on the third day after the onset of infection was associated with higher mortality in the PICU in the subgroup of patients with sepsis, among which 40% had septic shock. [9][10][11][12][13][14][15][16] The mechanisms by which the increase in FO influence the prognosis of patients with septic shock are still under debate, it is considered that a positive accumulated fluid balance is associated with the development of systemic hypoperfusion, tissue edema, respiratory and renal system failure; Studies carried out by Flori and collaborators concluded that persistently positive balance is deleterious in pediatric patients with acute lung injury, since it causes more days in mechanical ventilation and greater mortality, regardless of the magnitude of the oxygenation failure or severity of organic dysfunction. Along the same lines, Arikan and collaborators demonstrated similar findings, although in this study the time of ventilatory assistance was not considered.…”
Section: Discussionmentioning
confidence: 99%